STRATEGIC TRANSFORMATIONS: ASSESSING THE INTERPLAY OF DIGITAL COMMERCE, TRADITIONAL TRADE, AND EMERGING MARKET TRENDSIN THE GLOBAL BUSINESS LANDSCAPE - Alfiana Alfiana; Listiana Sri Mulatsih; Al-Amin; Muhamad Stiadi; Dede Gustian (International Journal Of Humanities, Social Sciences And Business (INJOSS), 2023)
In this comprehensive study titled "Strategic Transformations: Assessing the Interplay of Digital Commerce, Traditional Trade, and Emerging Market Trends in the Global Business Landscape," we embarked on a multifaceted exploration of the dynamic forces reshaping the global business environment. We delved into the complex interplay between digital commerce, traditional trade practices, and emerging market trends using empirical data and a rigorous analytical approach. Our research revealed a profound shift in how businesses operate and consumers engage with the marketplace. We found that once considered optional, digital commerce has evolved into an imperative for businesses seeking to remain competitive in the 21st century. This transformation extends beyond adopting online platforms; it encompasses the digitalization of supply chains, data-driven decision-making, and integrating emerging technologies such as Artificial Intelligence (AI) and Blockchain. Furthermore, our findings highlighted the intricate coexistence and convergence of digital and traditional trade practices. Businesses increasingly adopt hybrid models and omnichannel strategies to cater to diverse consumer preferences. This strategic adaptation allows them to leverage the strengths of both digital and traditional methods while remaining agile in response to emerging market trends. Sustainability emerged as a paramount concern, shaping consumer choices and driving businesses to embrace eco-conscious practices. The study underscores the need for businesses to view sustainability not as a mere trend but as a fundamental driver of their strategic decisions. Our research provides valuable insights for businesses, policymakers, and stakeholders navigating this transformative landscape. It contributes to the ongoing discourse on the future of commerce, offering practical implications and a roadmap for strategic decision-making in a world where the digital and traditional realms of business intersect and evolve.